A case of topical rapamycin effective for postsurgical hypertrophic scar of superficial lymphatic malformation with possible quality-of-life improvement - Yuki Isozaki; Motoi Kato; Naoko Fujita; Shota Tojo; Masahide Fujiki; Azusa Watanabe; Shoji Watanabe (Wolters Kluwer Medknow Publications, 2022)
Lymphatic malformation (LM) of the body surface causes symptoms such as bleeding, pain, lymphatic leakage, or infection of the lesion, usually treated with surgical resection and sclerotherapy, with limited efficacy. The vesicles of the body surface tend to recur after surgical resection and may cause lymphatic leakage, which could be long term a burden for patients, eventually decreasing their quality of life. In recent years, the efficacy of orally administered mammalian target of rapamycin inhibitor (rapamycin) has been reported for LM and other vascular anomalies but few are reported in the East Asian population. We report the case of a Japanese female with intractable gluteal LM that was successfully treated with topical rapamycin for postoperative recurrence and hypertrophic scarring.